UJI AKTIVITAS ANTIPIRETIK EKSTRAK ETANOL UMBUT BATANG ROTAN (Calamus rotang L.) TERHADAP MENCIT PUTIH JANTAN (Mus musculus) - Inderiyani Inderiyani; Sulastri Herdaningsih (Jurnal Komunitas Farmasi Nasional, 2021)
Rattan plant (Calamus rotang L.) is a plant that widely used by the people of Kapuas Hulu, West Kalimantan to treat diseases, as food and craft raw materials. Rattan plants contain flavonoids and alkaloids as secondary metabolites which are thought to have antipyretic activity. The purpose of this study was to determine the antipyretic activity of ethanol extracts of rattan stem umbut induced by 5% peptone. This research uses white mice (Mus musculus) male webster swiss strain as a test animal. The study was conducted using 5 test groups, the negative control group (aquadest), positive control (paracetamol 65 mg / KgBB), ethanol extract of rattan stem extract at a dose of 0.25 g / KgBB; 0.5 g / KgBB and 1 g / KgBB. Mice were induced with 5% peptone solution subcutaneously, then after an increase in rectal temperature ≥ 0.6◦C (fever) mice were treated with oral test solutions. The rectal temperature was measured using a digital thermometer in the 30th, 60th, 90th, 120th, 150th and 180th minutes. The results showed a group of ethanolic extracts of rattan stem at dose 0.25 g / KgBB; 0.5 g / KgBB and 1 g / KgBB had significant differences in the negative control group (p<0.05) with the percentage of antipyretic activity respectively at 117.17%; 154.76% and 226.19%. The conclusion of this research is the ethanol extract group of rattan stem extracts with a dose of 0.25 g / KgBB; 0.5 g / KgBB and 1 g / KgBB have antipyretic activity.